Comparing of K-Means, K-Medodis and Fuzzy C-means Cluster Method for Analog Modulation Recognition - Kaya, Y.; Avcı, D.; Gedikpınar, M. (My University, 2019)
A modulation process is required to transmit analog signals with higher quality. Modulation is the process of transporting the signal by another carrier signal. This study aims to process analog signals. Using 200 samples of each of the six types of analog modulation modules. Nowadays these are Amplitude Modulation (AM), Double Side Band (DSB), Upper Side Band (USB), Lower Side Band (LSB), Frequency Modulation (FM) and Phase Modulation(PM) respectively. In the study an intelligent clustering method has been developed. The 5th level Discrete Wavelet Transform (DWT), Norm Entropy and Energy properties of AM, DSB, USB, LSB, FM and PM analog modulated signals have been removed during feature extraction phase. The results have been compared using K-Means, K-medoid and Fuzzy C-means (FCM) algorithms using a feature vector of 6x2x1200 obtained at the feature extraction stage and carrying out smart intelligent clustering for recognition. The most successful result has been obtained with FCM of 85.75%.
Keywords: Mühendislik; Elektrik ve Elektronik; Bilgisayar Bilimleri; Yazılım Mühendisliği